2014
DOI: 10.1111/maec.12154
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and feeding patterns of juvenile parrotfish on algal‐dominated coral reefs

Abstract: By the consumption of algae, parrotfishes open space for young coral settlement and growth, thus playing a central role on the maintenance of coral reefs. However, juvenile parrotfish ecology is often overlooked due to the difficulty discerning species during this phase. Herein, we present the first attempt to investigate changes in habitat use and diet that happen to juveniles of the Redeye parrotfish Sparisoma axillare, focusing on four zones within an algal‐dominated reef: the macroalgal beds, back reef, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 70 publications
(132 reference statements)
2
13
1
Order By: Relevance
“…Recently, macroalgal habitat has become a major focus of research in tropical systems, and research has shown that macroalgal beds can be more important than seagrass beds as a nursery area for juvenile fishes [8,37,42]. Macroalgal beds have high levels of epiphytes and invertebrate epifauna [42,72], which are often the target prey for juvenile parrotfishes [15,17,45]. Considering the potential importance of macroalgal beds for coral reef fishes, there has been relatively little research conducted in these habitats under the framework of understanding how macroalgal beds may contribute to abundance patterns of coral reef fishes [8,30,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, macroalgal habitat has become a major focus of research in tropical systems, and research has shown that macroalgal beds can be more important than seagrass beds as a nursery area for juvenile fishes [8,37,42]. Macroalgal beds have high levels of epiphytes and invertebrate epifauna [42,72], which are often the target prey for juvenile parrotfishes [15,17,45]. Considering the potential importance of macroalgal beds for coral reef fishes, there has been relatively little research conducted in these habitats under the framework of understanding how macroalgal beds may contribute to abundance patterns of coral reef fishes [8,30,37].…”
Section: Discussionmentioning
confidence: 99%
“…Most research describes parrotfish juveniles as only "Scarus spp." when exploring juvenile habitat patterns [41][42][43][44], but see [45]. Typical studies may be dealing with 2-3 dozen species of parrotfishes, especially in the Indo-Pacific.…”
Section: Introductionmentioning
confidence: 99%
“…Brazil has an extensive coastline of about 8,000 km where mangroves, seagrass-and seaweed beds and coral reefs are present. Connectivity patterns of fish as mobile links between habitats are sparsely studied in Brazil, with very little information on connectivity dynamics, and how different habitats might be of importance to reef fishes (but see Moura et al 2011, Feitosa and Ferreira 2014, Aschenbrenner et al 2016. For most reef fish species, there are critical knowledge gaps in nursery habitat use and ontogenetic habitat shifts.…”
Section: Introductionmentioning
confidence: 99%
“…provide high structural complexity and a large surface for associated invertebrates and epiphytic filamentous algae(Venekey et al 2008). These traits might make seaweed beds a high-value nursery habitat for herbivorous fishes that feed on filamentous algae, such as juvenile parrotfishes(Feitosa and Ferreira 2014) and juvenile acanthurids(Dias et al 2001). Also invertivorous fishes have been recorded in high abundances in seaweed beds, probably because of the large number of invertebrates associated with the seaweeds(Evans et al 2013, Tano et al 2016.…”
mentioning
confidence: 99%
“…Diet analyses also provide insight towards broader subjects such as population dynamics (Braga et al 2012), habitat use (Feitosa and Ferreira 2015), evolution (Collar et al 2009), energy flow between ecosystems (Baxter et al 2005), and conservation (Alcaraz et al 2015;Donadelli et al 2015). Characterizing the diet of early-stage fishes is particularly important because this is when fish grow most rapidly and undergo ontogenetic shifts that are critical to survival.…”
Section: Introductionmentioning
confidence: 99%